Donor genetic determinant of thymopoiesis rs2204985 impacts clinical outcome after single HLA mismatched hematopoietic stem cell transplantation - Tsamadou, Chrysanthi; Gowdavally, Sowmya; Platzbecker, Uwe; Sala, Elisa; Valerius, Thomas; Wagner-Drouet, Eva; Wulf, Gerald; Kröger, Nicolaus; Murawski, Niels; Einsele, Hermann; Schaefer-Eckart, Kerstin; Freitag, Sebastian; et al. (Bone marrow transplantation, 2022)
A common genetic variant within the T cell receptor alpha (TCRA)-T cell receptor delta (TCRD) locus (rs2204985) has been recently found to associate with thymic function. Aim of this study was to investigate the potential impact of donor rs2204985 genotype on patient’s outcome after unrelated hematopoietic stem cell transplantation (uHSCT). 2016 adult patients were retrospectively analyzed. rs2204985 genotyping was performed by next generation sequencing, p < 0.05 was considered significant and donor rs2204985 GG/AG genotypes were set as reference vs. the AA genotype. Multivariate analysis of the combined cohort regarding the impact of donor’s rs2204985 genotype indicated different risk estimates in 10/10 and 9/10 HLA matched transplantations. A subanalysis on account of HLA incompatibility revealed that donor AA genotype in single HLA mismatched cases (n = 624) associated with significantly inferior overall- (HR: 1.48, p = 0.003) and disease-free survival (HR: 1.50, p = 0.001). This effect was driven by a combined higher risk of relapse incidence (HR: 1.40, p = 0.026) and non-relapse mortality (HR: 1.38, p = 0.042). This is the first study to explore the role of rs2204985 in a clinical uHSCT setting. Our data suggest that donor rs2204985 AA genotype in combination with single HLA mismatches may adversely impact post-HSCT outcome and should thus be avoided.
Gesehen am 05.09.2023